Harvey Friedman's research on the foundations of mathematics - Friedman, Harvey, 1948-; Harrington, L. A. (Studies in logic and the foundations of mathematics, 1985)
This volume discusses various aspects of Harvey Friedman's research in the foundations of mathematics over the past fifteen years. It should appeal to a wide audience of mathematicians, computer scientists, and mathematically oriented philosophers.